The Presence of Religiosity in Augusto dos Anjos - Costa, Miguel (2023)
The purpose of this article is to promote a reflection on the presence of religiosity in Augusto dos Anjos' work, listing and analyzing the elements and symbols present in it that can be understood as religious in nature. To enrich the discussion, works such as Márcia Peters Sabino (2005), who discusses the presence (or not) of religiosity in the poet's work, arguing that he promoted the deconstruction of religious symbols and themes, and Maria Olívia Garcia Ribeiro de Arruda (2009), who, when discussing the poem A um carneiro morto, brings an analysis that associates it more with a historical context than with a religious theme. Through a partial analysis of some excerpts from poems quoted by Sabino and a detailed analysis of the poem A um carneiro morto, quoted by Arruda, this work proposes an alternative version of analysis to those of the aforementioned authors.